Using Smart Apps Creator (SAC) as an Android-Based Learning Multimedia in Improving the Students’ Vocabulary Achievement - Hasrullah Hasrullah; Baso Jabu; Maemuna Muhayyang (PT ARRUS Intelektual Indonesia, 2024)
The aim of this research was to explain the extent to which the use of SAC as the Android-based learning multimedia is effective in improving the students’ vocabulary achievement of the seventh-grade students at SMPN 3 Topoyo. It used a quantitative approach with pre-experimental design taking all the seventh-grade students and 30 students as the sample of this research and employed a vocabulary test as its instrument to collect the data. The results of this research reveal that the students’ vocabulary achievement got significant improvements which the students’ mean score for the Pre-test was 46.33 and the students’ mean score for the Post-test was 81.67. The Post-test mean scores exceeded 70, achieving the learning objectives. From the findings of the research, it can be concluded that the results demonstrated significant improvement in students' vocabulary achievement, with a substantial increase in the number of students achieving high levels of achievement. Therefore, the use of SAC was considerably effective in enhancing students’ vocabulary achievement and fostering a positive learning atmosphere.